Statistical evaluation of PV system performance and failure data among different climate zones. (August 2019) - Halwachs, M.; Neumaier, L.; Vollert, N.; Maul, L.; Dimitriadis, S.; Voronko, Y.; Eder, G.C.; Omazic, A.; Mühleisen, W.; Hirschl, Ch.; Schwark, M.; Berger, K.A.; et al.
Abstract: The research project INFINITY focuses on design improvements for PV system components operating in different climatic regions. This topic gained pertinence in recent years due to increased installation rates worldwide with the highest growth rates in non-moderate climates. As PV components are not optimized to the respective climate zone, the target of the project is to gather failure data from PV installations in various climate zones. A standardized data input was achieved by using an extended format of the IEA PVPS Task 13 failure survey, allowing to enter PV system and failure information in rich detail. The components' and failure structure were elaborated by combining input from reliability workshop proceedings, PVPS Task 13 and project partners' experience in PV reliability testing. These structures were mapped into a database to collect and prepare the input for further statistical analysis. Collected data was filtered, offering a tidy data set of 1048 samples from 340 sub-systems from 45 countries worldwide. After data filtering, a power loss evaluation, a cluster analysis and a trend analysis were performed. This paper presents results of comparing PV module failures in different climate zones starting with a range of PV systems installed in the 1970s, to recently installed systems. Highlights: Comparison of PV module failures in different climate zones. 1048 failures from 340 sub-systems in 45 countries all over the world. Prevailing failures in the main climate zones (A-D) were identified. A cluster analysis shows typical combinations of failures in various climate zones. A trend analysis indicates different time to failure in individual climate zones.